Growth and Characterization of GaxIn1-xSb Thin Films for Infrared Detectors - B. Barman, Partha (Asian Journal of Chemistry, 2010)
Growth of GaxIn1-xSb (x = 0.1 to 0.5) thin films was carried out using hot wall epitaxy system on high purity quartz glasses and high resistive silicon as substrates. The source material for the growth of film was grown in the laboratory using vertical Bridgmen method in microprocessor controlled high temperature furnance. The grown films were characterized using grazing angle X-ray diffraction analysis and found to be polycrystalline in nature. XPS studies on the films showed non-stoichiometry compared to the bulk crystals. Band gap measurements using FTIR confirms the formation of energy gap in IR region, but the value does not exactly tally with the expected value of x. SEM studies on the films confirm the formation of pits on the surface which attributes to the nonstoichiometry in the films. Electrical characterization of the film, viz., Vander Pauw resistivity, Hall-mobility, surface carrier concentration, etc. measurement is under progress to study the interplay between the microstructure and electronic properties of polycrystalline semiconducting thin films. Finally Au/GaxIn1–xSb Schottky diodes were fabricated on the grown films and electrically characterised for IR detectors.